2011
DOI: 10.1027/0227-5910/a000086
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Announcement on Facebook

Abstract: Suicide notes on online social networks may allow for suicide prevention via the immediate intervention of other network users. But it is not yet clear to what extent suicide notes on online social networks actually induce copycat suicides. These effects deserve future evaluation and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 7 publications
0
69
0
8
Order By: Relevance
“…All but five of the identified SNS studies reported on participant data, with the remaining studies including one systematic review, one general literature review, two pieces discussing SNS in the context of clinical practice, and a descriptive networking study. Ages ranged between 12-85 years; however, with the exception of the systematic review paper [22], the two case study reports [54,59], and the analysis of online support group postings [60], all included studies focused on young people (eg, those aged 25 years or younger).…”
Section: Resultsmentioning
confidence: 99%
“…All but five of the identified SNS studies reported on participant data, with the remaining studies including one systematic review, one general literature review, two pieces discussing SNS in the context of clinical practice, and a descriptive networking study. Ages ranged between 12-85 years; however, with the exception of the systematic review paper [22], the two case study reports [54,59], and the analysis of online support group postings [60], all included studies focused on young people (eg, those aged 25 years or younger).…”
Section: Resultsmentioning
confidence: 99%
“…11 The existence of "pro-suicide" sites on the Internet and in social media 12 may further increase risk by providing details of various ways to commit suicide, as well as evaluations ranking these methods by effectiveness, amount of pain involved and length of time to produce death. [13][14][15] Our primary objective was to present the patterns of suicide among children and adolescents (aged 10-19 years) in Canada. studies describing the implementation of the ICD-10 in 2000 to understand trends in mortality between the ICD-9-CM and ICD-10 concluded that there was no effect on the continuity of suicide data.…”
mentioning
confidence: 99%
“…Even, people are unwilling to help his/her Facebook friend what are the factors that stimulate Facebook friends to provoke a vulnerable friend to commit suicide. This domain need furthers study as a number of projects and programs have been taken to reduce depression and prevent suicide using Facebook [7,8]. These initiatives are optimistic as Facebook gives unique opportunity to prevent depression as more than a quarter of the global population are connected here.…”
Section: Discussionmentioning
confidence: 99%